1976
DOI: 10.1172/jci108578
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal order of genes controlling the major histocompatibility complex, properdin factor B, and deficiency of the second component of complement.

Abstract: A B S T R A C T The relationship of the genes coding for HLA to those coding for properdin Factor B allotypes and for deficiency of the second component of complement (C2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…Low factor B has been noted previously to be associated with C2 deficiency (19), and it is shown that the genes for factor B and C2 are closely linked on the sixth chromosome (20). Our findings regarding factor B are of particular interest in that they suggest two populations of CZdeficient patients4ne with low normal CH50 levels and normal factor B levels, the other with low CH50 levels and low factor B levels.…”
Section: Discussionsupporting
confidence: 72%
“…Low factor B has been noted previously to be associated with C2 deficiency (19), and it is shown that the genes for factor B and C2 are closely linked on the sixth chromosome (20). Our findings regarding factor B are of particular interest in that they suggest two populations of CZdeficient patients4ne with low normal CH50 levels and normal factor B levels, the other with low CH50 levels and low factor B levels.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, AIO/B18 has been found in most patients with C2D (2,29.30), including 4 ( 1 , I 2,3 1,32) of the 7 aforementioned individuals with C2D-SLE in whom HLA studies have been reported. A n even more significant linkage disequilibrium has been shown between the C2" and HLA-D loci (33,34), with C2" and HLA-B tentatively mapped on opposite sides of HLA-D (35)(36)(37). Histocompatibility genes have also been linked with those controlling synthesis of factor B (36)(37)(38).…”
Section: Aio Aw24 Aio Aio a 2 Aio A 2 Aio Aio Aio A 2 Aw24mentioning
confidence: 99%
“…A n even more significant linkage disequilibrium has been shown between the C2" and HLA-D loci (33,34), with C2" and HLA-B tentatively mapped on opposite sides of HLA-D (35)(36)(37). Histocompatibility genes have also been linked with those controlling synthesis of factor B (36)(37)(38). The levels of factor B in patient Vi T and his 8 immediate relatives, however, showed no apparent relationship to C or HLA phenotypes or inheritance; rather, the results of these and other studies of factor B levels in C2D homo-and heterozygotes ( I , 6, 8, 12, 39) would seem to indicate an acquired, instead of inborn, basis for the decreases observed.…”
Section: Aio Aw24 Aio Aio a 2 Aio A 2 Aio Aio Aio A 2 Aw24mentioning
confidence: 99%
“…The structural locus for BF is closely linked to HLA in man (23). No crossover has yet been observed between C2*QO and BF (24) or C2 and BF (10). Finally, the loci for C2, BF, C4A, and C4B are thought to be close to HLA-D and HLA-DR with no observed recombination between them (25).…”
Section: Introductionmentioning
confidence: 99%